Aplikasi Mobile Trading Monex Guna Mendukung Customer Relationship Management - Hans Andre Martinus Supit; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACT            The growth of smartphone users in Indonesia is increasing every year. With the present era of disruption and digitalization also infrastructure development is increasingly sophisticated, causing consumer behavior to also experience shifts or changes. In conducting online trading transactions, informative, innovative and secure online trading applications will provide more benefits and help the company not only to survive in competition but also grow to be better companies. The needs of accurate information system and faster news should be adjusted with the growth of the information technology. Innovative Customer Relationship Management (CRM) strategy is increasingly needed by companies to grow. Applications are one way that companies can use as part of CRM.             This research will examine the usefulness and convenience of MIFX Mobile trading applications for customers and as part of CRM applications that can help the company grow for the long term. This research uses qualitative descriptive and uses purposive sampling technique by interviewing three types of informants directly related to the application in their daily life. The results of the interviews and the data that have been obtained will be processed and verified by using triangulation system of data sources, methods and theories. The results of this study are expected to assist customers in transacting and useful for companies in taking holistic CRM application approach and development strategy for future growth.